Dasysiphonia adriatica sp. nov. (Delesseriaceae, Rhodophyta), a new red algal species from the North Adriatic Sea (Mediterranean Sea) - WOLF, MARION A.; SCIUTO, KATIA; BUOSI, ALESSANDRO; ORLANDO-BONACA, MARTINA; FORTIČ, ANA; SFRISO, ADRIANO (Mediterranean Marine Science, 2024)
Dasysiphonia is a genus of the family Delesseriaceae (Rhodophyta) including 9 taxonomically accepted species, among which only the non-indigenous Dasysiphonia japonica has been documented from the Adriatic Sea (Mediterranean). This invasive species is native to Hokkaido Island (Japan) and was introduced to Europe and the Mediterranean Sea through imports of the commercial Pacific oyster Magallana gigas. In this study, we describe a new species belonging to the genus Dasysiphonia, collected in the Mediterranean Sea. This new taxon was sampled in Slovenian coastal waters; its thalli were analysed using both molecular and morphological approaches and it was compared with the other known species. Moreover, samples of the invasive D. japonica were collected from different Venice Lagoon (Italy) sites and used for comparison with the new taxon. The phylogenetic reconstruction, based on the plastid rbcL gene, clearly distinguished the new Slovenian entity from all the known Dasysiphonia species, including the ones recently transferred from the sister genus Dasya. These results indicate that the Slovenian samples represent a new species, hereby named Dasysiphonia adriatica sp. nov.